Древнейшие орехотворки из раннего мела Забайкалья (Hymenoptera, Cynipoidea, Archaeocynipidae fam. n.) - Расницын, А.П.; Ковалев, О.В. (Вестник зоологии, 1988)
A new family is established to include genera Archaeocynips gen. n. (type-species: A. villosa sp. n., included species: A. major sp. n.) and Dahurocynips gen. n. (type-species D. dahurica sp. n.).